Estimação da difusividade térmica em produto aquecido por condução baseado em problema inverso - Gontijo, Danúbia Lucas Meira (2023)
The sterilization operation traditionally used in the food industry has been known for a long time and is still widely used in the conservation of canned food products. Knowledge of the value of the heat transport property thermal diffusivity is very important in order to define the required heat treatment time and also to allow better control of the process in the face of variations in the temperature of the autoclave. This work presents the mathematical model that was developed and tested in the matlab/simulink™ application in order to estimate the value of thermal diffusivity. The model was used to simulate the temperature behavior of the studied food product based on a value adopted for the thermal diffusivity. The results obtained were validated by comparison with those available in the literature and showed good adherence to the latter, with deviations of less than 5ºC in the worst case.